Antimicrobial effect of tunta (Solanum juzepczukii) on Salmonella enterica subspecies enterica serovar Typhimurium - Garcia Castro, Raul Alberto (2021)
The objective of the study was to investigate the antimicrobial activity of tunta on Salmonella enterica subspecies enterica serovar Typhimurium. A natural isolate of this bacterium was used that was resistant to chloramphenicol. The experiment required the preparation of a standard solution of 0,8 g / ml of tunta extract. The Kirby Bauer technique was used for the antimicrobial evaluation of the tests and the Duraffourd scale to measure the level of sensitivity. Resulting, for the ten technical repetitions of the experimental group, an average halo of 10,40 mm and a standard deviation of 0,63 of DHI (level of limit sensitivity, according to said scale). In conclusion, our work shows evidence that tunta has an antimicrobial effect at a borderline sensitivity level on Salmonella enterica subspecies enterica serovar Typhimurium. After more in-depth research, this derivative of Solanum Jueepczukii could become an alternative for the development of antibiotics of natural origin and allow a sustainable development of Andean cultures.